Abnormal cardiac signs after Fontan type of operation: indicators of residua and sequelae. Issue 1 (January 1989) - Leung, M P; Benson, L N; Smallhorn, J F; Williams, W G; Trusler, G A; Freedom, R M
Abstract : Among 74 survivors of the Fontan type of operation abnormal cardiac signs were detected in 46 (62%) at postoperative examination. The findings were analysed in relation to the state of the cardiovascular system of these patients. Cyanosis was present in 10 (13.5%) patients. The causes of cyanosis included residual interatrial shunt (six patients), acquired pulmonary arteriovenous fistulas (three patients) and acquired systemic-to-pulmonary vein communication (one patient). Signs of chronic fluid retention were detected in six (8%) patients. In four of them the fluid retention was related to conduit obstruction and in the remaining two it was secondary to severe subaortic stenosis in one and atrioventricular valvar regurgitation in the other. Organic heart murmurs were heard in 29 (39%) patients. The aetiologies of these murmurs were multiple. They included aortic valve regurgitation (eight patients), subaortic stenosis (seven patients), atrioventricular valvar regurgitation (five patients), pulmonary valve regurgitation (five patients), residual Blalock-Taussig shunt (two patients), residual ventricular septal defect (two patients), residual communication in the main pulmonary artery which had been ligated but not divided (one patient), and left ventricular to right atrial shunting (one patient). Cardiac rhythm disturbances of varying aetiology were noted in 23 (31.1%) patients. Sixteen (21%) had supraventricular arrhythmias and seven (9.5%) had conduction abnormalities. The present review suggests that among survivors of the Fontan type of operation abnormal cardiac signs are indicators of residua or sequelae or both of the native cardiovascular anomalies or surgical procedures.